5. The Evaluation Between Partial and Impartial Attitude - Ciobanu Luminiţa (Sciendo, 2020)
Docimology is based on knowledge from the field of psychology and pedagogy. There are several functions of the didactic evaluation, related to their social and personal relevance. The interpretive evaluation involves a degree of subjectivism which, however, can be diminished by experience, patience and permanent self-control. The proposed evaluation methods will be applied simultaneously, with the objectification of the relevance of each one and with maximum sense of responsibility on the part of the evaluator.